La inclusión educativa, social y laboral de los jóvenes con discapacidad en la Universidad Laica VICENTE ROCAFUERTE de GUAYAQUIL - Bert Valdespino, Juana Emilia (2015)
The complex and multifactorial nature of inclusive policies, equity and social justice is disclosed and so is the challenge assumed by Universidad Laica VICENTE ROCAFUERTE (ULVR). The analysis starts with the study of specialized bibliographic sources and the use of theoretical methods intended to guide inclusive education practices for disabled people and their impact on higher education. An empirical research was conducted to explore a study group intentionally selected to enhance these results. In this regard, the instruments that were designed made it possible to do interviews to teachers and surveys to disabled students who work at different companies. As a result of the initial diagnosis, an integrated set of procedures has been integrated to the training process at ULVR. They materialize the inclusive approach taken, helping to characterize the current state of educational inclusion of young people in the university.